Ocular paraneoplastic syndromes - Kozicka, Katarzyna; Kubicka-Trząska, Agnieszka; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Ocular paraneoplastic syndromes are rare, autoimmune diseases characterized by the presence of circulating antiretinal antibodies leading to retinal damage. Paraneoplastic retinopathy is associated with abnormalities in electroretinography and visual field testing, as well as progressive vision loss. Paraneoplastic retinopathy can be divided into cancer-associated retinopathy, most commonly associated with small-cell carcinoma of lungs and breast cancer and melanoma-associated retinopathy, which occurs in patients with cutaneous melanoma. In cancer-associated retinopathy, the presence of antiretinal antibodies and ocular symptoms usually precede the diagnosis of primary malignant tumor, whereas melanoma-associated retinopathy typically manifests after the diagnosis of melanoma. Treatment of paraneoplastic retinopathy involves autoimmune response suppression using high doses of systemic corticosteroids, intravenous immunoglobulins, plasmapheresis or biological therapy. Although a number of treatments are available, the prognosis for visual improvement in patients with paraneoplastic retinopathy remains unclear.